MOTIVASI BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU TERHADAP KANJI - Rozi saputra; Hana Nimashita; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research is about learning motivation kanji on students of Japanese Language Education Study Program University of Riau . The purpose of this research is to find out how much the learning motivation students, what factors affecting the learning motivation students, and to know the response of students toward kanji in Japanese. Respondents in this research are 112 students of Japanese Language Education Study Program University of Riau. This research is used quantitative descriptive method. The result of this research shows that the learning motivation student is considered to be higher as much as 78.36%. In this research known that the factors were affecting the learning motivation students about kanji, are materials and method of learning, media and facilities of learning, teacher’s attitude, and the presence of friends. Student’s response are, 1) 69% student said that kanji is the likeable lesson. 2) 100% student said that kanji is important to learned, 3) 67% student said that learning kanji is not boring. 4) 95% student said that kanji is unique.Key words : motivation, learning motivation kanji